The Effect of Organizational Citizenship Behavior, Jobs Characteristic, and Burnout on Turnover Intention - Suwandi, Suwandi; Badrianto, Yuan (Ilomata International Journal of Management, 2024)
The study aims to determine how the influence of Organizational Citizenship Behavior, Jobs Characteristic, and Burnout on Turnover Intention (Case study Line Carrey Cahil Cavany Main Assy PT Indonesia Epson Industry) The sampling method used is a saturated sampling method with a sample of 75 respondents. Data collection using questionnaires with Likert measurement scales. The method used in this study is using Structural Equation Modeling (SEM) Analysis with Smartpls 3.0 software The tests used are outer model analysis, inner model analysis and hypothesis test. The results of the study explained that organizational citizenship behavior did not significantly affect turnover intention with a p-value of 0.727 t-statistic value 0.350, jobs characteristic had a positive and significant effect on turnover intention with a p-value of 0.000 t-statistic value of 8.225, burnout had a positive and significant effect on Turnover intention with a P-value of 0.012 T-Statistic value of 2.530. Policies related to career development, compensation, and employee welfare need to be improved so that employees feel valued and motivated to stay in the company. This can ultimately reduce the level of turnover intention in the company.